2018
DOI: 10.3389/fphys.2018.00989
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Diabetic Retinal Microaneurysm Perfusion Parameters Based on Computational Fluid Dynamics Modeling of Adaptive Optics Scanning Laser Ophthalmoscopy

Abstract: Diabetic retinopathy (DR) is a leading cause of vision loss worldwide. Microaneurysms (MAs), which are abnormal outpouchings of the retinal vessels, are early and hallmark lesions of DR. The presence and severity of MAs are utilized to determine overall DR severity. In addition, MAs can directly contribute to retinal neural pathology by leaking fluid into the surrounding retina, causing abnormal central retinal thickening and thereby frequently leading to vision loss. Vascular perfusion parameters such as shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 43 publications
5
37
0
Order By: Relevance
“…This allows the calculation of otherwise unmeasurable parameters such as wall shear stress and perfusion pressure. This information, if estimated accurately, would prove indispensable in deciding the likelihood that a given vessel or lesion will progress to lack of perfusion or development of other abnormalities . Such techniques can similarly be applied to study less severe structural abnormalities described above such as altered tortuosity or branching …”
Section: Scientific Advances With Ao Imaging: Vessel Structurementioning
confidence: 99%
See 1 more Smart Citation
“…This allows the calculation of otherwise unmeasurable parameters such as wall shear stress and perfusion pressure. This information, if estimated accurately, would prove indispensable in deciding the likelihood that a given vessel or lesion will progress to lack of perfusion or development of other abnormalities . Such techniques can similarly be applied to study less severe structural abnormalities described above such as altered tortuosity or branching …”
Section: Scientific Advances With Ao Imaging: Vessel Structurementioning
confidence: 99%
“…This information, if estimated accurately, would prove indispensable in deciding the likelihood that a given vessel or lesion will progress to lack of perfusion or development of other abnormalities. 67,68 Such techniques can similarly be applied to study less severe structural abnormalities described above such as altered tortuosity or branching. 69 In addition to microaneurysms, AO can be used to image other characteristic pathologies with high resolution, such as neovascularisation, hard exudates, haemorrhages, cotton wool spots, and intraretinal cysts.…”
Section: Microaneurysms and Other Lesions In Diabetesmentioning
confidence: 99%
“…Recent advances in imaging technology through AOSLO enable differentiating the thrombus-filled region from the perfused region in MAs. Bernabeu et al [ 27 ] reported that on AOSLO imaging thrombi are more frequently observed in saccular-shaped MAs compared to fusiform-shaped MAs.…”
Section: Introductionmentioning
confidence: 99%
“…Although retinal imaging now enables us to reconstruct the geometries of individual MAs and to perform computational fluid dynamics (CFD) studies to quantify the haemodynamic metrics, such as shear rate and wall shear stress [ 27 ], no computational studies have been performed to predict the initiation and formation of a thrombus in MAs. The ability to predict the course of thrombus development in MAs and thereby potentially better understand the overall risk of DR worsening might help ophthalmologists to monitor the progression of DR and guide appropriate timing for clinical intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation